Tempo e fragmento : uma análise de A Visit from the Goon Squad, de Jennifer Egan - Silva, Anna Carolina de Almeida e (2020)
This dissertation proposes an analysis of the novel A Visit from the Goon Squad, by American writer Jennifer Egan, taking into account aspects such as the fragmentation of the narrative and the role of time as an actor in the novel and its performance in the characters' lives. The fragmented narrative can generate interesting discussions because it imposes an intrinsic transgression of the plot, both in terms of form and content. Therefore, this dissertation seeks to analyze how the novel questions the classic narrative linearity, establishing an uncertain space-time displacement, which creates developments in relation to its fragmentary composition. In this sense, reflections are made on the representations of time in contemporary narratives and how they can be relevant to the understanding of this element in the analyzed novel, especially with regard to the subversion of chronological narrative assumptions and the relation between time and character development. In addition, in this process, the passage of time makes evident the influence of other elements for the construction of this fragmentary structure, such as music and technology, which are analyzed based on discussions about time and fragment.